Manajemen Pemeriksaan Pajak secara Daring Studi Kasus KPP Pratama Depok Cimanggis - Hanifah Maulina; Selvi Selvi (Jurnal Ilmu Administrasi Publik, 2021)
The purpose of this study is to analyse how tax audit management in KPP Pratama Depok Cimanggis, to analyse fiscus constraints in tax audit management in KPP Pratama Cimanggis and to analyze efforts made in overcoming existing constraints. This study uses qualitative approach with observation techniques and in-depth interviews with staff of the tax examination section of KPP Pratama Depok Cimanggis, Academicians, and Taxpayers. The result of this study came to the conclusion that the management of tax checks is still not good. The obstacles faced are during the pandemic there are restrictions that cause communication to be disrupted and limited, and there are still many taxpayers who are checked because of a writing error at the time of reporting the tax return. In addition there is no smooth communication with the taxpayer and cannot see the situation that occurs in real place in the taxpayers place. Efforts are made in the face of obstacles that employees must coordinate more with teams that have the ability to approach with taxpayers by communicating well in order to discuss the problems. Advice for KPP Pratama Cimanggis to continue to develop effective communication technique add wifi/internet network so  that the  examination process can run smoothly and maximally.